ROLE OF SHIRODHARA WITH ASWAGANDHA OIL IN THE MANAGEMENT OF INSOMNIA - Kumar Mukesh; Kumar Pankaj; Mangal Gopesh; Sharma Shrinivas (International Journal of Applied Ayurved Research, 2017)
Shirodhara is an important therapeutic measure in Ayurvedic system of medicine because of its simple administration and efficacy in variety of life style disorders. Shirodhara is a purifying and rejuvenating therapy designed to eliminate toxins and mental exhaustion as well as relieve stress and any ill effects on the central nervous system. Shirodhara is a unique form of ancient therapy of pouring oil on the forehead from a specific height and for a specific period continuously and rythmatically. Allowing the oil to run through the scalp and into the hair. Now a day’s insomnia is a common problem in society. Insomnia is considered as Anidra in Ayurveda. Almost every person is indulging in VatavardhakAhara-vihara. In Anidra vitiated VataDosha is the main culprit. Oil therapy is best suitable for VataDosha. Aswagandha oil has Vataghna property. So, Shirodhara with Ashawagandha oil was selected for this work. Total 30 patients were randomly selected for this open study. Shirodhara was done for 45 minute on each participant for 14 consecutive days. Insomnia Severity Index (ISI) was used to evaluate the severity of insomnia as well as to determine the response to Shirodhara therapy. Data were collected at baseline, end of the treatment (day 14) and 4 week after the treatment ended (follow-up). Highly significant result was found in the study. Shirodhara with Ashawagnadha oil was beneficial for moderate to severe insomnia. Shirodhara is a effective therapy in the management of insomnia. In this therapy no side effect was noticed such as letharginess which are common in modern treatment.